2022
DOI: 10.1186/s12967-022-03621-2
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, genetic susceptibility, and Alzheimer's disease: a longitudinal study based on 475,813 participants from the UK Biobank

Abstract: Background The association between body mass index (BMI) and Alzheimer's disease (AD) remains controversial. Genetic and environmental factors are now considered contributors to AD risk. However, little is known about the potential interaction between genetic risk and BMI on AD risk. Objective To study the causal relationship between BMI and AD, and the potential interaction between AD genetic risk and BMI on AD risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Nordestgaard et al 105 suggested that low BMI is not a risk factor for AD and is not associated with an increased risk of developing AD. However, contradictory findings propose that higher BMI correlates with a decreased risk of AD among individuals sharing the same genetic susceptibility 106 . It has also been postulated that both high and low BMI could augment the risk of AD development 105 .…”
Section: Discussionmentioning
confidence: 99%
“…Nordestgaard et al 105 suggested that low BMI is not a risk factor for AD and is not associated with an increased risk of developing AD. However, contradictory findings propose that higher BMI correlates with a decreased risk of AD among individuals sharing the same genetic susceptibility 106 . It has also been postulated that both high and low BMI could augment the risk of AD development 105 .…”
Section: Discussionmentioning
confidence: 99%
“…There are many risk factors for the development of cognitive impairment in older adults; for example, excessive sleep duration increases the risk after adjusting for numerous relevant risk factors (Yuan et al, 2022a ), and those with a low BMI (< 23 kg/m 2 ) have a higher risk of developing dementia (Yuan et al, 2022b ). With the advent of an aging society, cognitive impairment occurrence will become more common (Afzal et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in midlife, especially before the age of 50, has been linked to an increased risk of dementia, whereas in late-life, the association between high BMI and dementia often reverses. 26, 27 Prior MR studies have revealed that genetic liability to AD is linked to lower BMI, 28, 29 highlighting the role of late-life weight loss as a prodromal factor for AD. Accumulating evidence suggests that AD pathology leads to impaired functions of the hypothalamic and other brain regions crucial for metabolic regulations, which contribute to weight loss in the early stages of AD.…”
Section: Discussionmentioning
confidence: 99%